2018
DOI: 10.1021/acs.jmedchem.8b00632
|View full text |Cite
|
Sign up to set email alerts
|

The Design, Synthesis, and Characterizations of Spore Germination Inhibitors Effective against an Epidemic Strain of Clostridium difficile

Abstract: Clostridium difficile infections (CDI), particularly those caused by the BI/NAP1/027 epidemic strains, are challenging to treat. One method to address this disease is to prevent the development of CDI by inhibiting the germination of C. difficile spores. Previous studies have identified cholic amide m-sulfonic acid, CamSA, as an inhibitor of spore germination. However, CamSA is inactive against the hypervirulent strain R20291. To circumvent this problem, a series of cholic acid amides were synthesized and test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 84 publications
1
22
1
Order By: Relevance
“…The observation that specific bile acids can potently inhibit C. difficile spore germination, combined with the finding that C. difficile germination mutants are impaired in their ability to colonize hamsters and cause disease [17][18][19] and have led to the proposal that bile salt analogs could be used to prevent C. difficile-associated disease. Consistent with this hypothesis, synthetic bile acid analogs have been developed that prevent C. difficile spore germination both in vitro 28,30,49 and during infection of mice, 50 suggesting that these antigermination agents could be developed for clinical use. Indeed, even subinhibitory doses of these agents reduce disease severity.…”
Section: Antigermination Strategies For Preventing C Difficile Infecmentioning
confidence: 94%
“…The observation that specific bile acids can potently inhibit C. difficile spore germination, combined with the finding that C. difficile germination mutants are impaired in their ability to colonize hamsters and cause disease [17][18][19] and have led to the proposal that bile salt analogs could be used to prevent C. difficile-associated disease. Consistent with this hypothesis, synthetic bile acid analogs have been developed that prevent C. difficile spore germination both in vitro 28,30,49 and during infection of mice, 50 suggesting that these antigermination agents could be developed for clinical use. Indeed, even subinhibitory doses of these agents reduce disease severity.…”
Section: Antigermination Strategies For Preventing C Difficile Infecmentioning
confidence: 94%
“…Administration of CamSA severely diminished the amount of recoverable CD vegetative cells in a dose-dependent manner. Importantly, CamSA was not effective against all strains of CD, in particular the outbreak-associated strain R20291 99 belonging to the RT027 ribotype. However, a phenyl amide analogue of CamSA was synthesized and demonstrated to be 225 times more potent at inhibiting R20291 CD spore germination compared to CDCA.…”
Section: Small Molecule Inhibitors Of C Difficile Toxinsmentioning
confidence: 95%
“…However, a phenyl amide analogue of CamSA was synthesized and demonstrated to be 225 times more potent at inhibiting R20291 CD spore germination compared to CDCA. 99 …”
Section: Small Molecule Inhibitors Of C Difficile Toxinsmentioning
confidence: 99%
“…Our previous work showed that a combination between cholic acid and heterocyclic scaffolds improved the antibacterial property ( Figure 1 ) [ 21 ]. In 2018, Sharma et al presented a new pyridinyl-substituted cholic acid analogue that was effective against an epidemic strain of Clostridium difficile ( Figure 1 ) [ 22 ]. Recently, Chuchkov et al prepared a hybrid structure between heterocycle penciclovir and cholic acid, and the product showed antiviral activity ( Figure 1 ) [ 23 ].…”
Section: Introductionmentioning
confidence: 99%